Hydro‐Geochemical and Sr Isotope Characteristics of the Yalong River Basin, Eastern Tibetan Plateau: Implications for Chemical Weathering and Controlling Factors. (1st March 2019) - Zhang, Xuan; Xu, Zhifang; Liu, Wenjing; Moon, Seulgi; Zhao, Tong; Zhou, Xiaode; Zhang, Jiangyi; Wu, Yao; Jiang, Hao; Zhou, Li
Abstract: Major ions and Sr isotope compositions of waters in the Yalong River basin in the eastern Tibetan plateau were investigated to explore the sources of dissolved loads and the controls on chemical weathering rates. Measured radiogenic 87 Sr/ 86 Sr ratios of water samples are most likely derived from the weathering of metamorphic carbonates or the Precambrian silicate rocks. Quantitative analysis of water geochemistry shows that carbonate weathering dominates the chemical characteristics of the river water. The chemical weathering rate of the whole Yalong River basin is calculated to be 7.6 ton·km −2 ·year −1 by silicate weathering and 44.7 ton·km −2 ·year −1 by carbonate weathering, which consumes 158.5 × 10 3 and 885.0 × 10 3 mol·km −2 ·year −1 of atmospheric CO2, respectively. The highest carbonate weathering rate (116.3 ton·km −2 ·year −1 ) in the Yalong River basins is observed from the basin with the steepest catchment average slope. This highest magnitude of carbonate weathering is comparable to the rates from catchments in the southern Himalayas. Positive relationships are observed between silicate weathering rates and both climatic (precipitation and temperature) and topographic (relief and slope) controls. The combined climatic and tectonic effects increase silicate weathering and counterbalance the dilution effect. However, the relationship between silicate weathering rate and climatic and topographic controls varies with hydrologic conditions. The rate for low‐discharge catchments is more closely related to climatic parameters, while the rate for high‐discharge catchments is more closely related to local topography. Key Points: The highest carbonate weathering rate in the Yalong River basin is similar to that of tectonic active catchments in the southern Himalayas High 87 Sr/ 86 Sr ratios in rivers of the eastern Tibetan plateau are discovered, which come from meta‐carbonates or the Precambrian silicates The sensitivities of silicate weathering rates to climatic and topographic factors are variable with different hydrologic conditions